Interaksi Sosial Anggota Komunitas LET S HIJRAH dalam Media Sosial Group LINE - Prasanti, Ditha; Indriani, Sri Seti (Jurnal The Messenger, 2017)
Communication is an aspect that can not be separated in everyday life. Unwittingly, humans interact with each other to meet the needs of this communication. One of the containers that can be used as a means of social interaction is community or group. Let's Hijrah is an Islamic community with 200 members in its LINE social media group. This is interesting to investigate. Based on the phenomenon, researchers are interested to lift Social Interaction of Membership Let's Hijrah Community in LINE Social Media . Researchers use qualitative research approach with virtual ethnography method. The results of this study indicate: (1) social interaction that occurs in members of the community Let's Hijrah in social media group LINE often lead to debates that lead to negative perceptions for its members; (2) topics discussed in LINE social media about anything related to Islamic jurisprudence.